2021
DOI: 10.5851/kosfa.2021.e15
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Different Storage Temperatures on the Physicochemical Properties and Bacterial Community Structure of Fresh Lamb Meat

Abstract: Upload this completed form to website with submission ARTICLE INFORMATION Fill in information in each box below Article TypeResearch article Article TitleEffects of different storage temperatures on the physicochemical properties and bacterial community structure of fresh lamb meat

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(16 citation statements)
references
References 66 publications
0
16
0
Order By: Relevance
“…There was a significant positive correlation between Pseudomonas and TVB-N content. Pseudomonas might play an important role in the production of TVB-N during cryopreservation of donkey meat ( Liang et al, 2021 ; Na et al, 2018 ).…”
Section: Resultsmentioning
confidence: 99%
“…There was a significant positive correlation between Pseudomonas and TVB-N content. Pseudomonas might play an important role in the production of TVB-N during cryopreservation of donkey meat ( Liang et al, 2021 ; Na et al, 2018 ).…”
Section: Resultsmentioning
confidence: 99%
“…A total of 40 longissimus lumborum muscles (24 h postmortem) were sampled at Beijing Hualian Group, Nanjing, China, and prepared as previously described [ 22 ]. Briefly, all samples were placed in insulated chilled boxes following slaughter and transported to the laboratory within 2 h. Fat and connective tissues were removed.…”
Section: Methodsmentioning
confidence: 99%
“…The application of sequencing for characterizing predominant microorganisms involved in the spoilage of pork has been reported previously [ 2 , 4 , 18 , 19 ]. In addition, it has been reported that the microbial communities in pork differed substantially upon storage at different temperatures [ 20 , 21 , 22 ]. However, since most previous studies have focused on the effects of storage at different chilled or superchilling temperatures (including 4 °C, −1 °C, −2 °C, and −3 °C) or different packaging treatments (e.g., modified atmosphere-packing), a comprehensive comparison of changes in the microbial composition and functional potential upon storage temperatures of −2 °C (superchilling), 4 °C (chilling), 10 °C (transportation or retail), and 25 °C (room temperature) is lacking.…”
Section: Introductionmentioning
confidence: 99%
“…Fresh meat is very conducive to the microbial growth because of its high water content, optimal pH and abundant nutrients (Liang et al, 2021), which will lead to the spoilage of fresh meat. The spoilage degree is closely related to the species and amount of bacteria under specific storage conditions (Kaur et al, 2021;Li et al, 2019;Mansur et al, 2019).…”
Section: Introductionmentioning
confidence: 99%